Working Safely in the Trades as Women: A Qualitative Exploration and Call for Women-Supportive Interventions - Curtis, Hannah M.; Meischke, Hendrika W.; Simcox, Nancy J.; Laslett, Sarah; Monsey, Lily M.; Baker, Marissa; Seixas, Noah S. (Frontiers in Public Health, 2022)
Background Construction work offers women economic advancement and self-fulfillment opportunities, but multiple barriers prevent their increased representation in the industry. This study used qualitative methods to identity key physical and psychosocial safety hazards affecting tradeswomen. Methods Three focus groups were held in 2015 with 19 tradeswomen in Washington State. Groups discussed workplace hazards and solutions to make the trades safer for women. Discussions were recorded, transcribed, and two independent reviewers analyzed themes. Results Participants identified myriad physical and psychosocial hazards including a dangerous work environment, inadequate personal protective equipment, gender discrimination, and fear of layoff for reporting concerns. Participants identified mentorship as a potential intervention to overcome some of these barriers. Conclusion Findings suggest that the industry's work environment can be hostile and unsupportive for women, contributing to tradeswomen's injury risk and psychological distress. Future research and interventions should focus on understanding the relationships between and mediating the negative impact of women's physical and psychosocial workplace hazards. Results from these focus groups inspired a randomized control trial to study the impact mentorship has on decreasing physical and psychosocial hazards for women in construction, and improving retention.